Experimental Warming Effects on Soil Respiration, Nitrification, and Denitrification in a Winter Wheat-Soybean Rotation Cropland. Issue 2 (19th January 2017) - Chen, Shutao; Liu, Yan; Zhai, Xiaoyan; Hu, Zhenghua
ABSTRACT: A field experiment was conducted to examine responses of soil respiration, nitrification, and denitrification to warming in a winter wheat ( Triticum aestivum L.)–soybean ( Glycine max (L.) Merr) rotation cropland. The results showed that seasonal variations in soil respiration were positively related to seasonal fluctuations in soil temperature. Seasonal mean soil respiration rates for the experimental warming (EW) and control (CK) plots were 3.98 ± 0.43 and 2.54 ± 0.45 μmol m −2 s −1, respectively, in the winter wheat growing season, and they were 4.59 ± 0.16 and 4.36 ± 0.08 μmol m −2 s −1, respectively, in the soybean growing season. There was a marginally significant level ( p = 0.097) for mean nitrification rates between EW and CK plots. Soil temperature and moisture accounted for 58.2% and 58.1% of the seasonal variations observed in the winter wheat and soybean plots, respectively.